Medium-term protocols for in vivo evaluation of chemical modifiers of carcinogenesis - Camargo, João Lauro Viana de [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1991)
Cancer development is a long-term multistep process which allows interventional measure before the clincial disease emerges. the detection of natural substances which can block the process of carcinogenesis is a important as the identification of anti-tumoral drugs since they might be used in chemoprevention of cancer in high-risk groups. In vivo rodent models of chemical caecinogenesis have been used to study plant-derived inhibitors of carcinofenesis such as indols, coumarins, isothiocyanates, flavones, phenols and allyl-sulfides. Since the standard in vivo rodent bioassay is prolonged and expensive, shorter reliable protocols are needed. Two in vivo medium-term protocols for evaluation of modifiers of carcinogenesis are presented, one related to liver and the other to bladder cancer. Both protocols use rats, last 8 and 36 weeks and are based on the two-step concept of carcinogenesis: initiation and promotion. The protocols use respectively the development of altered foci of hepatocytes expressing immunochistochemically the placental form of gluthation S-transferase and the appearence of pre-neoplastic urothelium and papillomas as the end-points. the use of these protocols for detection of plantpderived inhibitors of carcinogenesis appear warranted.
Keywords: carcinogenesis; chemoprevention; bladder cancer; liver cancer; plant; derived inhibitors